Study on the Molecular Mechanism of the Herbal Couple Sparganii Rhizoma-Curcumae Rhizoma in the Treatment of Lung Cancer Based on Network Pharmacology. (19th June 2021) - Dai, Shuying; Zhang, Gaochenxi; Zhao, Fangmin; Shu, Qijin
Abstract : Background . Lung cancer has a poor prognosis and a high mortality rate, and patients may develop multidrug resistance. Sparganii Rhizoma-Curcumae Rhizoma (HCSC), the classic herbal drug combination of traditional Chinese medicine (TCM), is commonly used in treating tumors, but its molecular mechanism is still unclear. Method . We explored the possible mechanisms underlying the antitumor effect of HCSC using network pharmacology. The bioactive components of HCSC and their targets were collected from the TCM Systems Pharmacology (TCMSP) database and PharmMapper. Gene Ontology (GO) and KEGG enrichment analyses were performed; the GeneMANIA platform was used for the functional enrichment analysis of the core targets and their neighboring genes. Molecular docking was performed between the bioactive components and core targets. HCSC freeze-dried powder was prepared, and the bioactive components were verified by liquid chromatography- (LC-) mass spectrometry (MS). Human lung adenocarcinoma H1975 cells were cultured to verify in vitro the molecular mechanism of action of HCSC in treating lung cancer, as predicted by network pharmacology. Finally, we used the Symmap database to predict the relationship between the herb and TCM syndrome. Result . A total of seven bioactive components were identified by network pharmacological analysis. Through enrichment analyses, it was found that the mechanism of action mainly involved mitochondrial-mediated caspase-dependent cell apoptosis signaling pathways. The results of molecular docking showed that the bioactive components in HCSC have a good affinity with the target proteins (ALB, BCL2L1, ESR1, HRAS, MAP2K1, MAPK14, and SIRT1). LC-MS confirmed that formononetin and bisdemethoxycurcumin were present in the HCSC freeze-dried powder, consistent with the prediction. The results of in vitro experiments on NCI-H1975 cells confirmed that HCSC can upregulate the mitochondrial-mediated caspase-dependent apoptosis signaling pathway by inducing the cleavage of caspase-3, caspase-9, and PARP, consistent with the network pharmacology prediction. Further, the qi deficiency and blood stasis associated with TCM syndrome can be treated with HCSC.